Was low atmospheric CO2 during the Pleistocene a limiting factor for the origin of agriculture? - Sage, R.F.
Agriculture originated independently in many distinct regions at approximately the same time in human history. This synchrony in agricultural origins indicates that a global factor may have controlled the timing of the transition from foraging to foodproducing economies. The global factor may have been a rise in atmospheric CO2 from below 200 to near 270 ^mol mol"^ which occurred between 15,000 and 12,000 years ago. Atmospheric CO2 directly affects photosynthesis and plant productivity, with the largest proportional responses occurring below the current level of 350 )xmol mor^ In the late Pleistocene, CO2 levels near 200 (imol mol"^ may have been too low to support the level of productivity required for successful establishment of agriculture. Recent studies demonstrate that atmospheric CO2 increase from 200 to 270 ^.mol mor' stimulates photosynthesis and biomass productivity of C3 plants by 25
Keywords: ORIGIN OF AGRICULTURE; CO2 ENRICHMENT; CROP DOMESTICATION; GLOBAL CHANGE; NEOLITHIC TRANSITION; PHOTOSYNTHESIS